The nomination of Rev. Kazimierz Rolewski as bishop of Katowice and the reasons for the refusal - Maciej Szczepaniak (Polonia Sacra)
Rev. Kazimierz Rolewski (1887–1936) — parish priest in the Archdiocese of Poznań, rector of the theological seminary, and radio preacher — remains an inspiring figure to this day, as evidenced by the ongoing beatification process. Many people remember him as a priest who refused to accept the episcopal nobleness. This article refers to this common opinion in light of the Vatican archives. It is an attempt to highlight the important character traits of the discussed figure, especially his humility and sincerity. Based on the source analysis method, the article presents facts about Rev. Rolewski before and after the proposal to take over the bishopric of Katowice. This article presents the genesis of the interest in the parish priest from Ostrów Wielkopolski as a candidate for the diocesan bishop in 1925–1926. It describes the circumstances of the negative decision made at the apostolic nunciature in Warsaw. The above piece, which attempts to highlight the character traits important for the discussed character — his humility and honesty — fills the current biographical gap of Rev. Rolewski.